Novel molecular mechanisms in Alzheimer’s disease: The potential role of DEK in disease pathogenesis - Greene, Allie N.; Solomon, Matia B.; Privette Vinnedge, Lisa M. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease and age-related dementias (AD/ADRD) are debilitating diseases that exact a significant physical, emotional, cognitive, and financial toll on the individual and their social network. While genetic risk factors for early-onset AD have been identified, the molecular and genetic drivers of late-onset AD, the most common subtype, remain a mystery. Current treatment options are limited for the 35 million people in the United States with AD/ADRD. Thus, it is critically important to identify novel molecular mechanisms of dementia-related pathology that may be targets for the development of new interventions. Here, we summarize the overarching concepts regarding AD/ADRD pathogenesis. Then, we highlight one potential molecular driver of AD/ADRD, the chromatin remodeling protein DEK. We discuss in vitro, in vivo, and ex vivo findings, from our group and others, that link DEK loss with the cellular, molecular, and behavioral signatures of AD/ADRD. These include associations between DEK loss and cellular and molecular hallmarks of AD/ADRD, including apoptosis, Tau expression, and Tau hyperphosphorylation. We also briefly discuss work that suggests sex-specific differences in the role of DEK in AD/ADRD pathogenesis. Finally, we discuss future directions for exploiting the DEK protein as a novel player and potential therapeutic target for the treatment of AD/ADRD.